Exercise of authority and political power: How to govern to build trust and hope in times of crisis? - Sagasti, Francisco (2022)
In this article, the former President of the Republic of Peru, Francisco Sagasti, develops five points that he considers were the main features of the approach to the exercise of authority and political power within the Transition and Emergency Government that he led. These criteria were respect for the Constitution and the laws, honesty and transparency, teamwork and coordination, use of evidence and reliable information, search for the common good, and democratic leadership.